A report on the practice in industry training in fish culture - De Leon, Elizabeth M. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1954)
Changes in solubility, pepsin digestibility and amino acid content of the proteins of rounds scad (Decapterus Macrosoma Bleeker) subjected to varying heat treatments prior to canning were determined to detect changes that occurred in fish proteins. Samples of round scad, which were steamed, canned raw and pre cooked then canned were used. Heat treatment of fish proteins was found to result in considerable decrease in protein content especially the salt-soluble fraction. The decrease observed with respect to these two parameters was highly dependent on the severity of heat applied. However, pepsin digestibility tests showed that canning rendered fish more digestible while steaming produced a reverse effect. An amino acid analysis of samples showed that steaming caused decreases in the amount of amino acids possibly because of the leaching out of moisture. The sample, which was canned raw, had a higher values for any given amino acids than that which was steamed prior to canning.
Report (Undergraduate, Fish Culture) College of Fisheries, University of the Philippines, 1976.
Keywords: Fish-culture.